Review dan Kritikal Jurnal: Keynes’ Theory of Liquidity Preference and His Debt Management and Monetary Policies - Faurani Santi (Jurnal Bisnis Darmajaya, 2015)
This article reviews the theory of Keynes relating to monetary policy, management of long-term debt, and liquidity of investment funds as written by Geoff Tilly in 2006 with entitled Keynes's Theory of Liquidity Preference and His Debt Management and Monetary Policies, and taken from the Cambridge Journal of Economics , Volume 30, pages 657-670.Results and conclusions derived from these journals is that the macro-economic conditions of country are determined by the long-term interest rates that may affect directly to investment, growth, and the unemployment rate.In this article also carried out a critical and review of the journal. The results of the review are agreed that the monetary policy of the government to stabilize the macro-economic conditions not necessarily be a panacea in solving the problems of macro-economy of country. This means that the macro policies of a general nature is not always a way out for resolving the problem, therefore it need  a sensitivity policy to solve problems, especially policies issued by factor conditions / situations, geographical, historical, and of course the factors of uncertainty of the country.Keywords: Keynes  theory, liquidity, debt management, and monetary policy